2018
DOI: 10.1097/tp.0000000000002287
|View full text |Cite
|
Sign up to set email alerts
|

Early TLR4 Blockade Attenuates Sterile Inflammation-mediated Stress in Islets During Isolation and Promotes Successful Transplant Outcomes

Abstract: Early TLR4 blockade protects islets from sterile inflammation-mediated stress sustained during isolation and promotes positive transplant outcomes. Our findings support the use of early TLR4 blockade during clinical islet isolation procedures to reduce pretransplant inflammation and improve transplant outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 49 publications
1
10
0
Order By: Relevance
“…OPN-305, the first humanized IgG4 monoclonal antibody against TLR-2 on monocytes, was tested in a randomized, double-blind, in-human phase I study [35]. In animal models, TAK242 pretreatment attenuated inflammation-mediated stress response and improved chronic pancreatitis and islet trans-plantation results [36]. Our results also support the combined use of TLR-2 and -4 antagonists in severely infected patients (Supporting Information Fig.…”
Section: Discussionsupporting
confidence: 66%
“…OPN-305, the first humanized IgG4 monoclonal antibody against TLR-2 on monocytes, was tested in a randomized, double-blind, in-human phase I study [35]. In animal models, TAK242 pretreatment attenuated inflammation-mediated stress response and improved chronic pancreatitis and islet trans-plantation results [36]. Our results also support the combined use of TLR-2 and -4 antagonists in severely infected patients (Supporting Information Fig.…”
Section: Discussionsupporting
confidence: 66%
“…In order to restore insulin independence after islet transplantation, more than one cadaveric pancreata are usually needed to achieve sufficient islets for one recipient 13 , 14 . One reason is that the inflammation stress during the islet isolation impairs islet viability and function 15 18 . The inflammatory signals produced during the isolation procedure can be further amplified through a positive feedback mechanism in the following ex vivo culture period before transplantation, leading to further damage to the islets and affecting transplantation outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…The inflammatory signals produced during the isolation procedure can be further amplified through a positive feedback mechanism in the following ex vivo culture period before transplantation, leading to further damage to the islets and affecting transplantation outcomes. Inhibiting the inflammatory stress during islet isolation is a potential approach to improving islet quality and quantity 15 . In the present study, we identified that CORM-2 effectively reduced the expressions of inflammation factors in the isolated islets, including TF , ICAM-1 , CCL2 , CXCL10 , TLR4 , IL-1β , IL-6 , and TNF-α ( Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Islet isolation and transplantation were performed as previously described with minor modifications. 17,18 Briefly, pancreases are perfused with 100-125μg/mL Liberase TL (Roche Diagnostics, Indianapolis, IN) and digested in a 37°C water bath for 18-22 minutes. After washing with HBS the crude digest is purified over a discontinuous density gradient, washed once more with HBS, and cultured overnight in RPMI 1640 (Corning; Corning NY) supplemented with 10% FBS, 10mM HEPES, and 1% penicillin-streptomycin solution.…”
Section: Methodsmentioning
confidence: 99%